PENGARUH PERUBAHAN ANGGARAN EFEKTIVITAS DAN EFISIENSI TERHADAP PENGGUNAAN DANA DESA DI DESA KECAMATAN LANGSA BARO KOTA LANGSA - Masriandi; Afrah Junita; Nasrul Kahfi Lubis (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2025)
This study aims to determine the effect of budget changes, effectiveness, and efficiency on the use of village funds in the village of Langsa Baro sub-district, Langsa city. This study is a type of quantitative research using primary data obtained through questionnaires and measured using a Likert scale. The population in this study used all villages in Langsa Baro sub-district as many as 12 villages. The sampling technique used stratified random sampling, the sample criteria in this study were the village head, village secretary, village treasurer, and head of government in Langsa Baro sub-district as many as 48 people. The analysis technique in this study used multiple linear regression analysis with the help of the IBM SPSS application. The results of this study indicate that the budget change variable has a positive and significant effect on the use of village funds, the effectiveness variable has a positive and significant effect on the use of village funds, and the efficiency variable has a positive and significant effect on the use of village funds. However, this study has limitations, including the limited coverage area only in Langsa Baro sub-district, so the results cannot necessarily be generalized to other areas with different conditions. Furthermore, this study focused only on the main variables. Therefore, further research is expected to expand the scope and include other relevant variables to obtain more comprehensive results.